ANALISIS GAYA BAHASA DALAM PUISI EPIGRAM 60 KARYA JOKO PINURBO (KAJIAN STILISTIKA) - Shinta Oktafiani; Heru Prasetyo; Munaris Munaris; Latifatul Azizah (FKIP Universitas Lampung, 2025)
Poetry is an intellectual expression that uses rhyme and a methodical framework to arouse emotions and stimulate the senses. Stylistics is the area of literary science that focuses on object- based style. Language style serves as the research object. One of the things that makes poetry better is linguistic style, which includes the author's viewpoint that enhances the writer's words or language. There are four categories of language styles: repetitious, connective, contrastive, and comparative. Examining the language types in Joko Pinurbo's collection of poetry